Slow stroke back massage (SSBM) therapy with lavender essential oil effectively lowers blood pressure - Iwan Sulis Setiawan; Tri Ismu Pujiyanto; Yunani Yunani; Eko Winarto (Universitas Aisyiyah Yogyakarta, 2023)
Hypertension is a global health problem that is a major factor causing cardiovascular disease and premature death. While pharmacological therapy is still the main choice, non-pharmacological therapies with minimal side effects, such as a combination of slow stroke back massage (SSBM) and aromatherapy, are expected to increase relaxation so as to increase the effectiveness of lowering blood pressure in hypertensive patients. This study aimed to test the effectiveness of SSBM therapy with lavender essential oil in lowering blood pressure in patients with primary hypertension. The research used a quasi-experiment method with a pretest-posttest design with a control group. In this study, the samples used were hospitalized patients with primary hypertension who met the inclusion and exclusion criteria, with as many as 40 respondents using purposive sampling techniques. Slow stroke back massage (SSBM) therapy with lavender essential oil significantly lowers blood pressure values in primary hypertensive patients compared to SSBM therapy with baby oil (P valueÂ 0.05). The mean difference in systolic and diastolic blood pressure in the intervention and control groups was 6.25 and 2.65, respectively. This therapy has been proven to be effective in lowering blood pressure in primary hypertensive patients. Therefore, hospital management may consider applying this nonpharmacological therapy to manage primary hypertension patients.